THE EFFECT OF GREEN INVESTMENT, INTELLECTUAL CAPITAL DISCLOSURE, AND CARBON EMISSION DISCLOSURE ON FIRM VALUE - Adira M. B. Azhari; David H. M. Hasibuan (Kesatuan Press, 2023)
This study evaluates the market performance of mining businesses listed on the Indonesia Stock Exchange from 2017 to 2021 concerning intellectual capital disclosure, carbon emission disclosure, and green investment.Secondary data for this study was from the Indonesia Stock Exchange/IDX (www.idx.co.id) and the Ministry of Environment and Forestry (www.proper.menlhk.go.id). The data were gathered through purposeful sampling. Based on a predefined set of criteria, 60 data sets from 12 mining companies were gathered over five years. The study's methodology included descriptive statistics and panel data regression.According to this study, disclosures regarding intellectual property did not affect value, green investments did not affect firm value, and disclosures about carbon emissions had a significant and favorable effect.